Rancang Bangun Pengisian Dan Pembuangan Air Kolam Ikan Berdasarkan Isi Volume Air Berbasis Sensor Water Level, Sensor Hujan Dan Arduino Uno - Chairul Indra Angkat; Ummul Khair; Imran Lubis (Universitas Harapan Medan, 2021)
Water management in fish farming ponds during the rainy season is very troublesome for cultivators,This is due to rainwater that enters continuously which can cause damage to grass and objects around the pond and can also cause fish to be dragged by the current and stranded out of the aquaculture pond.From the description of the problem, the authors conducted research by designing a system for draining and filling fish farming ponds that work automatically based on rainwater detection.The way this device works is that when the rain sensor detects raindrops, the tool will translate the rainy weather so that the tool will activate the drain pump.When the water level reaches the upper water level sensor, the device instructs the drain pump to drain the water in the aquaculture pond, the drain pump will stop when the level reaches the lower water level sensor. Furthermore, the tool will instruct the filling pump to fill water into the pool and the filling pump will stop when the water level reaches the normal water level sensor. By implementing this system, fish farming farmers can be helped to drain water from aquaculture ponds when heavy rains occur.